Analysis of dynamic reactivity by Monte Carlo methods: The impact of nuclear data. (December 2017) - Zoia, Andrea; Jouanne, Cédric; Siréta, Patricia; Leconte, Pierre; Braoudakis, George; Wong, Lindee
Highlights: We compute the dynamic reactivity of several reactor configurations (IPEN/MB-01, SPERT III and IV). We resort to Monte Carlo simulation with the Iterated Fission Probability (IFP) method. We single out some systematic discrepancies between computed and measured core reactivity. We determine the impact of nuclear data libraries on the obtained results. Abstract: We compute the dynamic reactivity of several reactor configurations by resorting to Monte Carlo simulation. The adjoint-weighted kinetics parameters are first determined by the Iterated Fission Probability (IFP) method, together with precursor decay constants, and the reactivity is then estimated by the inhour equation. When literature values are available for the reactivity as a function of the asymptotic reactor period, comparison with the Monte Carlo simulation findings allows validating the IFP algorithm and at the same time probing the accuracy of the nuclear data libraries used in numerical simulations. For our calculations we resort to the Tripoli-4 ® Monte Carlo code, developed at CEA, where IFP methods have been recently implemented. We perform a detailed analysis of the IPEN/MB-01 core, the SPERT III E-core, and the SPERT IV D-12/25 core, for which benchmark-quality reactor specifications have been published. We single out some systematic discrepancies between computed and measured core reactivity that might mirror possible inconsistencies in nuclear data libraries.